Analysis of complications among patients hospitalized in the Intensive Care Unit of the Upper Silesian Medical Centre after cardiac surgery in 2010-2011 - Gierek, Danuta; Kaczmarska, Adriana; Budziarz, Barbara; Cyzowski, Tomasz; Krzych, Łukasz; Gierek, Michał (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Background: Cardiac surgery operations are related to high risk of perioperative complications. 10-20% of patients require hospitalization in intensive care units mostly due to cardiac failure, respiratory failure, hypovolemic shock, septic shock, abdominal complications, and neurologic complications. Aim : The aim of the study was to analyze complications which led to admission to the Intensive Care Unit of the Upper Silesian Medical Centre in 2010-2011, after cardiac surgery. Material and methods: This study enrolled patients after cardiac surgery, who required hospitalization in the ICU in 2010-2011. The study was retrospective. The material for this study was medical documentation of the patients. We analyzed demographic data, reasons for admission to the ICU, and therapeutic routines. Results: In the ICU 32 patients were treated due to complications after cardiac surgery. The mortality rate among those patients was 65.6%. The most common complication was septic shock. Neurologic complications were rare. Other complications were pneumonia and surgery complications. Health condition was assessed on admission according to APACHE II and values were significantly lower among patients who survived. The TISS-28 score was significantly higher among patients who died. Conclusions : The mortality rate among patients with complications after cardiac surgery is still significant. Acute bowel ischemia, which often is the cause of septic shock, is a factor responsible for a lethal outcome. Complications after cardiac surgery are related to high costs of therapy and deterioration of patients’ life quality.